PENGARUH LINGKUNGAN KERJA DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP TINGKAT KETERLIBATAN GURU DAN TENAGA KEPENDIDIKAN DALAM PROGRAM DAN KEGIATAN SEKOLAH DI SMAN 1 MUARA WAHAU - Anggy Hanggara; Hediati Mahardika; Norkumala Dewi; Azzainil; Laili Komariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to analyze the effect of work environment and principal leadership on the level of teacher and education staff engagement in school programs and activities at SMAN 1 Muara Wahau. The research used a quantitative approach with explanatory research design. Data were collected through questionnaires using a Likert scale distributed to teachers and education staff. The data were analyzed using multiple linear regression analysis. The results show that the work environment has a significant positive effect on engagement, principal leadership has a significant positive effect on engagement, and both variables simultaneously influence the level of engagement. These findings indicate that creating a supportive work environment and strengthening principal leadership are essential to improving participation in school programs.